Thermal Rectification Characteristics of Graphene Nanoribbons of Asymmetric Geometries. (19th December 2016) - Iwata, T.; Shintani, K.
ABSTRACT: The rectification of heat in graphene nanoribbons (GNRs) of asymmetric geometries is investigated by means of nonequilibrium molecular dynamics (NEMD). Two kinds of geometries of GNRs are addressed; a trapezoidal or T-shaped step is inserted halfway through a GNR in its longitudinal direction. The thermal conductivities (TCs) of the GNRs in the two longitudinal directions, forward and backward, are calculated making their width and temperature change. It is revealed that the thermal rectification ratio (TRR) of T-shaped GNRs are larger than those of trapezoidal GNRs and that the characteristics of heat transport in such asymmetric GNRs can be understood by considering the local phonon density of states (DOSs).